Highly uniform indicator-mediated SERS sensor platform for the detection of Zn2+. Issue 20 (9th February 2016) - Jin, Liangliang; She, Guangwei; Mu, Lixuan; Shi, Wensheng
Abstract : An indicator-mediated surface-enhanced Raman scattering (SERS) sensor platform with highly uniform SERS sensitivity was fabricated by modifying 4-mercaptopyridine (4-MPY) molecules as an indicator onto the surface of Ag nanoparticles that were anchored onto a silicon wafer. Abstract : An indicator-mediated surface-enhanced Raman scattering sensor platform with highly uniform SERS sensitivity was fabricated by modifying 4-mercaptopyridine molecules onto the surface of Ag nanoparticles that were anchored onto a silicon wafer. The present SERS sensor platform realized quantitative detection of Zn 2+ .